FACTORS IMPACTING LIQUIDITY OF BANKS: AN EMPIRICAL STUDY FROM THE BANKING SECTOR IN THE UAE - Kapur, Manoj; Banerjee, Arindam; Malik, Kunjana (Indian Journal of Finance and Banking, 2022)
The primary purpose of this research is to substantiate the factors that impact the liquidity of the banks in the UAE. This research paper is an extension of the thesis that the primary author has undertaken to prove the test of significance and provide concrete evidence that the identified idiosyncratic and market related factors have significant impact on the liquidity risk for the banks in the UAE. The primary author has performed linear regression to identify the relation of the dependent and independent variables and once the test of significance is proved, the factors have been ranked using MURAME approach as part of ultimate thesis research objectives (MURAME approach is not forming part of this research paper). The research paper focusses on top 10 banks in the UAE and the study spans from 2010 to 2019. The study employs idiosyncratic factors like Deposit growth, NPL, CAR, ROA and market factors like GDP, Inflation, Unemployment, Oil prices and studies its relationship on dependent factor i.e., liquidity. Series of diagnostic tests are performed to find the impact of liquidity on idiosyncratic and market related factors. JEL Classification Codes: E58, G32, G38.